Physical Activity Level of White Collar Office Workers in Penang, Malaysia - Seow, Veronica, Wan Ying; Thirumalaya, Balaraman (INTI International University, 2019)
Though the health benefits of Physical Activity (PA) have been proven, the level of physical inactivity has been increasing gradually in the adult population, especially office workers who spend most of their working time in sitting in a chair. But there is insufficient data regarding the physical activity level of office workers in Penang, Malaysia.